Southeast Asia and the Middle East - Carool Kersten (International Institute of Islamic Thought, 2010)
As part of a growing interest in global and transnational patterns connecting different parts of the Muslim world, scholarship on Islam in Southeast Asia, which has long suffered from what Robert Hefner once called a “double marginalisation” in the work of both Islamicists and Asianists, has made considerable progress in mapping the networks connecting Dar al-Islam’s eastern geographical peripheries with its perceived Middle Eastern “heartland.” And while Cornell historian Eric Tagliacozzo notes that several studies deal with the history of the commercial, educational, and religious exchanges between the Hijaz and insular Southeast Asia, making good for the “paucity of historiography of this particular transregional dialogue,” he sees his edited volume as filling the lacuna on “what the parameters of this long-distance dialogue between civilizations have meant over the centuries” (p. 1). Using Fernand Braudel’s notion of longue durée as a rubric, he has grouped the collected essays under the respective headings of “The Early Dimensions of Contacts,” “The Colonial Age,” “The First Half of the 20th Century,” and “Into Modernity.” ...